Illustrated checklist of mileewine leafhoppers (Hemiptera: Cicadellidae: Mileewinae) of China, with descriptions of four new species - Yang, Mao-Fa; Meng, Ze-Hong; He, Qing; Dietrich, C. H. (Zootaxa, 2014)
Four new species of Mileewini, Mileewa houhensis Yang, Meng & He, sp. nov., M. xiaofeiae Yang, Meng & He, sp. nov., M. yangi Yang, Meng & He, sp. nov. and Ujna liangae Yang, Meng & He, sp. nov. are described and illustrated. Mileewa nigricauda Yang & Li, 1999 is placed as a junior synonym of M. dorsimaculata (Melichar, 1902); three of the previously described Chinese Mileewa are transferred to the genus Ujna. These are Ujna harpa (Yang & Li, 2004) comb. nov., U. nigrimaculata (Yang & Li, 2004) comb. nov., and U. puerana (Yang & Meng, 2010) comb. nov. M. lynchi (Distant, 1918) is recorded as new for China. A checklist of Mileewini leafhoppers of China along with photograph of their dorsal habitus is provided.